Cold room system for Dewan Makan Siswa UiTM / Faitulmuen Burhanudin and Mohd. Rashid Halim - Burhanudin, Faitulmuen; Halim, Mohd. Rashid (2002)
Our main objective is to study case for cold room at Dewan Makan Siswa UiTM. The main reason that we choose cold room at Dewan Makan Siswa UiTM is because there are many complained about the poor quality meats and vegetables that were served at Dewan Makan Siswa UiTM. From our observations, there are many factors that can caused this problem. The system that use for the cold room is an old version that haved to be upgraded to maintaince the cooling efficiency. The size also not setting well to it compressor and evaporator power that need for the cold room. The other reason is the temperature that need to be adjusted as the types of goods installed in the cold room. There is also no specified cold room for the vegetables and fruits like the chiller cold room. In diis research project report we have tried to solved die problem that happen. We also tried to calculate the suitable size and the temperature for the cold room. This report usually look out the needs for higher food quality at Dewan Makan Siswa UiTM